Effect of Grapevine Age on the Aroma Compounds in ‘Beihong’ Wine - Du, Gang; Zhan, Jicheng; Li, Jingyuan; You, Yiling; Zhao, Yu; Huang, Weidong (South African Journal of Enology and Viticulture, 2016)
The main aim of this study was to determine the influence of grapevine age (3, 6 and 12 years) on the aroma compounds in ‘Beihong’ wine. Aroma compounds in wine were analyzed by solid-phase microextraction gas chromatography-mass spectrometry (SPME-GC/MS). Thirty-three (33) volatile compounds were identified and quantified. The majority of aroma compounds were esters (20) and the concentration of these totaled 90.63-92.82% (w/w) of the total aroma compounds; particularly, ethyl octanoate and ethyl decanoate. Through the descriptive analysis aroma profile for ‘Beihong’ wine, the highest aroma contribution was from the fruity and floral series. As the age of the grapevine increased, the concentrations of total volatiles and total odor activity values (OAVs) of the wines significantly increased (p < 0.001). This suggests that grapevine age could affect berry composition, enhance the content of wine aroma compounds and improve wine quality.